Expression of L-type amino acid transporter 1 (LAT1) in neuroendocrine tumors of the lung - Kaira, Kyoichi; Oriuchi, Noboru; Imai, Hisao; Shimizu, Kimihiro; Yanagitani, Noriko; Sunaga, Noriaki; Hisada, Takeshi; Kawashima, Osamu; Iijima, Hironobu; Ishizuka, Tamotsu; Kanai, Yoshikatsu; Endou, Hitoshi; et al. (Pathology, research and practice, 2008)
Amino acid transport systems play an important role in cellular proliferation. L-type amino acid transporter 1 (LAT1) has been associated with tumor growth, and is highly expressed in the established tumor cell lines and primary human neoplasms. In this study, we investigated the expression of LAT1 to evaluate the malignant potential and prognostic significance in neuroendocrine (NE) tumors of the lung. Twenty-one surgically resected, large cell neuroendocrine carcinomas (LCNEC), 13 small cell lung cancers (SCLC), five atypical carcinoids (AC), and 10 typical carcinoids (TC) were enrolled in the study. LAT1 expression and Ki-67 labeling index of the NE tumors were analyzed by immunohistochemical staining. LAT1 was overexpressed in 52.4% of the LCNEC, in 46.2% of the SCLC, and in 25% of the AC. LAT1 expression in LCNEC was significantly associated with lymph node metastasis and poor outcome. Moreover, a significant correlation was found between LAT1 expression and Ki-67 in both LCNEC and SCLC. Expression of LAT1 tended to increase from low-grade to high-grade NE tumors. The present results suggest that LAT1 may play a significant role in cellular proliferation, lymph node metastasis, and poor outcome in patients with NE tumors of the lung.